Advances and Future Directions of Diagnosis and Management of Pediatric Abusive Head Trauma: A Review of the Literature - Iqbal O'Meara, AM; Sequeira, Jake; Miller Ferguson, Nikki (Frontiers in Neurology, 2020)
Abusive head trauma (AHT), broadly defined as an injury of the skull and intracranial contents as a result of inflicted injury, represents a persistent and significant source of disease burden in the pediatric community. Despite medical advances in definitions and diagnosis, early recognition of AHT remains a major challenge for modern clinicians. Given this difficulty, the published incidence of 10 to 30 per 100,000 infants per year is likely a considerable underestimate; a major problem when the estimated healthcare burden of AHT can be measured in billions of dollars, to say nothing of the lifelong neurocognitive disability that victims can experience. Current management of AHT in the acute phase has not advanced far beyond supportive care, therefore prevention and early recognition are crucial. New diagnostic algorithms and imaging modalities hold some promise, but these generally come into play after AHT has already occurred; education and recognition of warning signs in the primary care setting hold the most promise for true prevention. Care of AHT is evolving as well; historically, ICP-driven therapy has been a mainstay of treatment, however emerging data may shed light on the nature of AHT progression, necessitating more nuanced treatment than simple avoidance of elevated intracerebral pressure. Seizure prophylaxis has similarly been a historic standard of care, but studies have failed to show long-term benefits in functional outcomes. As practice evolves, the role of additional modifying environmental factors may come to light. The role of stress in the neuroinflammatory response is an area of burgeoning research and may provide new areas of intervention. Our treatment of AHT may soon see other changes as well, as new emerging studies concerning ICP monitoring may further elucidate the nature of AHT as a longitudinal disease process. Finally, education and practice changes geared toward early recognition in the prehospital phase, both for practitioners and early responders, may prove instrumental to earlier intervention.